Advances in the Influence of EGFR Mutation on the PD-L1 Expression in Non-small Cell Lung Cancer - Xiaoyu ZHI; Weiwei LI; Shaowei WANG; Jinliang WANG (Chinese Journal of Lung Cancer, 2019)
Researches on the inhibitors of programmed death-1 (PD-1) and programmed death-1 ligand (PD-L1) enjoy considerable breakthroughs in recent years, which has brought relative changes in the therapeutic model of non-small cell lung cancer (NSCLC) at an unexpected speed. However, it seems that PD-1/PD-L1 inhibitors are less effective in patients with epidermal growth factor receptor (EGFR) mutation than those without. Previous studies have shown that the expression rate of PD-L1 on tumor cells is correlated with the therapeutic effect of PD-1/PD-L1 inhibitors. Yet, there is no complete agreement on the effect of EGFR mutation on PD-L1 expression. In this review, relevant studies will be summarized with an expectation of making some contributions to basic researches and to the clinical treatment.